Ekoteologi dalam Pemikiran Seyyed Hossein Nasr dan Relasi Agama-Masyarakat - Vella, Nurul Khorina Seci; Ahmad Rizal, Derry (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2024)
Environmental issues have become a major concern in recent years. In fact, the impact that is always felt is the widespread pollution, the problem of waste that is increasingly accumulating until the closure of several landfills (TPA) in Indonesia. This paper tries to reopen our insight into environmental concerns in the concept of Seyyed Hossein Nasr. The research method used is qualitative based on library research with descriptive analysis. This paper also discusses how religion-society relations and environmental concerns become social actions that should be of common concern. It focuses on our understanding of environmental care as God's creatures who maintain stability between nature and life. Khalifah, as the basis of Seyyed Hossein Nasr's perspective, is a task that should be carried out by every human being. But in reality, attention to the environment is secondary in life, so that the impact felt today is extreme climate change and increased pollution.